Upgrade tecnológico em economias emergentes: Uma abordagem comparativa para Brasil e China (2001-2020) - Oliveira, Graciely Aquino de (Universidade Federal de São Carlos, 2024)
Brazil and China are considered important references for industrialization in developing economies, however, they have followed different industrial policy strategies and macroeconomic contexts in recent decades, which has led these economies to follow different paths. The objective of this paper is to develop and analyze comparative indicators of technological upgrading for Brazil and China during the period from 2001 to 2020, offering a more accurate and qualitative perspective for understanding these two national configurations. To achieve this, a comparative analysis of technological upgrading indicators between Brazil and China was conducted, based on the theoretical assumptions and indicators suggested by Radosevic and Yoruk (2015, 2017): intensity of technological upgrading, scope of technological upgrading, and interaction with global technology. A calculation based on the Euclidean distance (ED) was used to arrive at the value of technological upgrading and its component indices. As a result it was observed that both economies started the period with similar indicators, but that China showed superior performance in most components throughout the period.
Technology Upgrading in Emerging Economies: A Comparative Approach for Brazil and China (2001-2020)
Keywords: Upgrade tecnológico; Desenvolvimento econômico; Brasil; China; Technological Upgrade; Economic Development; Brazil; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIA INDUSTRIAL; 9. Indústria, Inovação e Infraestrutura